(untitled) (Razi Medical Journal, 2026)
This study aims to assess the nutritional status of patients with celiac disease, investigate the prevalence of nutrient deficiencies, and analyze the impact of the disease on weight, body mass index (BMI), and vitamin and mineral levels. A cross‑sectional study was conducted involving 70 patients diagnosed with celiac disease. Data were collected through questionnaires that included information on medical history, anthropometric measurements, and nutritional factors. The results were analyzed using SPSS software. The study revealed that the proportion of females was higher than that of males (58.6% vs. 41.4%). The most represented age group was between 26 and 35 years. Deficiencies in iron, calcium, and several vitamins were identified among the patients. These findings indicate a significant prevalence of nutrient deficiencies in individuals with celiac disease, underscoring the need for tailored dietary treatment plans and improved nutritional education.